Oral Abstracts 2021
DOI: 10.1136/bmjno-2021-anzan.10
|View full text |Cite
|
Sign up to set email alerts
|

010 Real-world experience with ocrelizumab in the MSBase registry – Australian RRMS cohort

Abstract: compared to 1/14 LGI1-Ab+patients(p=0.0024) and 1/12 healthy controls. Conclusion Neuropathic pain may be present in both LGI-Ab + and CASPR2-Ab+patients, and is immunotherapy responsive. Serum IgG from CASPR2-Ab+patients more frequently bound sensory neurons and dorsal root ganglia, suggesting pathophysiological differences which may underlie the more severe pain in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The low rates of patients discontinuing OCR due to AEs suggest favorable long-term tolerability, which together with its sustained efficacy, contributes to the high persistence observed in real-world cohorts. [15][16][17][18] Fatality rates in the clinical trials remained below those observed in postmarketing settings, as well as the expected fatality rates (0.37-0.90 per 100 PY) observed in real-world MS cohorts. 18,19 It should be noted that postmarketing patients tend to have older age, longer disease duration, higher proportion of progressive MS, and a greater number of previous disease-modifying treatments (DMTs) and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low rates of patients discontinuing OCR due to AEs suggest favorable long-term tolerability, which together with its sustained efficacy, contributes to the high persistence observed in real-world cohorts. [15][16][17][18] Fatality rates in the clinical trials remained below those observed in postmarketing settings, as well as the expected fatality rates (0.37-0.90 per 100 PY) observed in real-world MS cohorts. 18,19 It should be noted that postmarketing patients tend to have older age, longer disease duration, higher proportion of progressive MS, and a greater number of previous disease-modifying treatments (DMTs) and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 It should be noted that postmarketing patients tend to have older age, longer disease duration, higher proportion of progressive MS, and a greater number of previous disease-modifying treatments (DMTs) and comorbidities. 15 Whereas IRRs were among the most frequently reported AEs with OCR, most patients did not experience IRRs, and the majority were mild to moderate, decreased with the number of infusions, and were effectively managed through administering premedication, adjustment to infusion rates, and symptomatic treatment. An appropriate premedication protocol with mandatory methylprednisolone and antihistamines, as well as an optional analgesic, was followed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a recent smaller US cohort ( 17 ), patients with RMS in CONFIDENCE had similar mean EDSS and fewer patients in CONFIDENCE were treated with first-line ocrelizumab. With respect to ocrelizumab treated patients documented in the global MSBase registry ( 2 ), CONFIDENCE populations had similar age profiles. Patients with RMS tended to have a higher EDSS and proportions of patients without prior therapy were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Ocrelizumab (Ocrevus®) is a monoclonal antibody that specifically binds to CD20, modulating the immunopathogenesis of MS by depleting CD20 + B-cells. As the first anti-CD20 monoclonal antibody approved for the treatment of RMS and PPMS, ocrelizumab remains the only approved treatment for PPMS to date ( 2 , 3 ). Pivotal trial data shows that treatment with ocrelizumab has significant effects on slowing disease progression, annualized relapse rate and magnetic resonance imagery outcomes, with no signal of a higher rate of serious infections, compared with interferon in patients with RMS and placebo in patients with PPMS ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one-third of patients in the pivotal CLARITY trial switched to cladribine tablets from interferon-beta or glatiramer acetate 3 ; however, neither DMF nor teriflunomide treated patients were enrolled as these treatments were approved after the completion of CLARITY. Real-world cohorts published recently report on patients switching from all first-line treatments, including DMF and teriflunomide, however, in a descriptive manner, 17 , 18 or in very small numbers. 19 …”
Section: Discussionmentioning
confidence: 99%